PARACETAMOL DETECTION AT A GRAPHITE PASTE MODIFIED ELECTRODE BASED ON PLATINUM NANOPARTICLES IMMOBILISED ON Al-SBA-15 COMPOSITE MATERIAL - NGO, Thi Thanh Hien; FORȚ (LADIU), Carmen Ioana; PHAM, Thanh Huyen; TURDEAN, Graziella Liana (Studia Universitatis Babeș-Bolyai Chemia, 2020)
A composite material was obtained by immobilizing platinum nanoparticles (Pt-NPs) within an ordered mesoporous structure Al-SBA15 (having improved acidity due to the presence of Al). This was used for preparing a graphite paste modified electrode (Pt/Al-SBA-15-GPE), which was applied for paracetamol (PA) detection. The obtained electrode was investigated by electrochemical methods (e.g. cyclic voltammetry, CV and electrochemical impedance spectroscopy, EIS), in order to estimate the electrochemical parameters, which were compared with those of GPE unmodified electrode. Square-wave voltammetry (SWV) was used to obtain the analytical parameters of Pt/Al-SBA-15-GPE for PA detection. The good analytical parameters recommend the composite mesoporous material (Pt/Al-SBA-15) to be used for preparing modified electrodes for PA detection in real samples.